2022
DOI: 10.3389/fendo.2022.935390
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolic Dysfunction-Associated Fatty Liver Disease With Left Ventricular Diastolic Function and Cardiac Morphology

Abstract: Background and AimNon-alcoholic fatty liver disease (NAFLD) is closely related to cardiovascular diseases (CVD). A newly proposed definition is metabolic dysfunction-associated fatty liver disease (MAFLD), which was changed from NAFLD. The clinical effect of this change on abnormalities of cardiac structure and function is yet unknown. We aimed to examine whether MAFLD is associated with left ventricular (LV) diastolic dysfunction (LVDD) and cardiac remolding and further identify the impact of different subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…From the initial search, 2619 studies were identified. Ultimately, 38 of them were included in the systematic review [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Furthermore, 31 of them were found eligible for meta-analysis ( Figure 1 ), since 7 of the studies included in the systematic review did not have the required quantitative data.…”
Section: Resultsmentioning
confidence: 99%
“…From the initial search, 2619 studies were identified. Ultimately, 38 of them were included in the systematic review [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Furthermore, 31 of them were found eligible for meta-analysis ( Figure 1 ), since 7 of the studies included in the systematic review did not have the required quantitative data.…”
Section: Resultsmentioning
confidence: 99%
“…LS-associated metabolic syndrome was associated with left ventricular diastolic dysfunction and cardiac remodeling. These studies provide theoretical support for precise cardiovascular dysfunction prevention in patients with LS [ 45 , 46 ]. A slightly contradictory conclusion was reached by an observational study by Cardoso et al, who followed DM2 patients for 5.5 years and identified a protective effect of a higher CAP value on mortality, even in the cardiovascular mortality subgroup.…”
Section: Possible Clinical Applicability Of Qnusmentioning
confidence: 93%
“…This meta-analysis also found that concomitant metabolic risk factors and liver disease severity were independently associated with abnormalities in cardiac function. Finally, Peng et al [ 66 ]. found that MAFLD was associated with left ventricular diastolic dysfunction and cardiac remodeling (including greater inter-ventricular septum thickness and left ventricular posterior wall thickness, as well as larger left atrial diameter and greater left ventricular hypertrophy), especially in patients with coexisting T2DM or obesity and in those with moderate-to-severe hepatic steatosis.…”
Section: Consensus Statements and Recommendationsmentioning
confidence: 99%